Construction of a frontier in the west of the bishopric of Chiapa and Soconusco, 1650-1810. An approach from the GIS-H - Navarro-López, América Alejandra (Revista Geográfica de América Central., 2022)
It was undertook an historical and cartographic investigation out on the limits of the border region of the Tuxtla Desert-Xiquipilas Valley, western frontier of the bishopric of Chiapa and Soconusco, in the south of New Spain, adjacent to the Captaincy General of Guatemala. The period of study begins in 1650, with the process of Composiciones de Tierras (1643) underway, and ends in 1810, at the end of the colonial period, with a territorial organization by Intendencias. From the analysis of documentary sources and cartography of the time, information was obtained and processed in a methodology designed for the orientation of geographic information systems towards history. The research allows us to analyze historically and geographically the processes of territorial appropria- tion through the use of land as strategies of demarcation and occupation in a frontier region.